PROPOSISI KONDISIONAL DALAM IKLAN LAYANAN MASYARAKAT MASA PANDEMIC COVID-19 - Firmina A. Nai (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2021)
Although this research does not focus on linguistic rules which are the main media of advertising, the discussion about construction is one of the important aspects in this research. One sentence construction is a proposition or reasoning. Samhis Setiawan (2021) by citing experts asserts that a proposition is a speech or statement that describes several conditions that are not necessarily true or false in the form of a news sentence. Proposition is a term used in logical analysis. These circumstances and events generally involve the person or person referred to by the utterance in the sentence. There are 3 forms of propositions, namely categorical propositions, hypothetical propositions, and disjunctive propositions. One type of hypothetical proposition is called a conditional proposition. which states a condition of a dependent relationship between two propositions. This relationship shows that one proposition must follow the other propositions because of certain conditions. That is, if the conditions are met then the truth occurs. Conversely, if the conditions are not met then the truth does not occur. A conditional proposition is usually marked with “If…Then”, “If…Then”, “If…Then”, “If…Then”, “Suppose…Then”. Through conditional propositions and the meanings contained in them, the Government offers good conditions so that people live healthily during and after the Covid-19 Pandemic.